Ischemic optic neuropathy. Pathogenesis, clinical features, diagnostics and treatment - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Ischemic optic neuropathy is a common cause of visual loss in the older population. This disease is classified into anterior and posterior type according to the location the lesions. The anterior type is due to transient nonperfusion or hypoperfusion of the ciliary circulation in the optic nerve head. The etiology of this disease is multifactorial. The most important risk factors for developing anterior ischemic optic neuropathy (AION) include hypertension, nocturnal hypotension, diabetes mellitus, atherosclerosis and small cup in the optic disc. AION presents with sudden painless loss of vision, pale edema of the optic disc, afferent papillary defect and visual field defects, typically in lower quadrants. Posterior ischemic optic neuropathy (PION) is a rare condition and diagnosis of it usually is made only after other causes of a retrobulbar optic neuropathy have been excluded. There are three distinct subtype of PION: perioperative, arteritic and nonarteritic. They are characterized by acute visual loss, variable visual field defects, relative afferent pupillary defect and normal optic disc.